Midterm outcome of implantable left ventricular assist devices as a bridge to transplantation: Single-center experience in Japan. Issue 5 (May 2015) - Kimura, Mitsutoshi; Kinoshita, Osamu; Nawata, Kan; Nishimura, Takashi; Hatano, Masaru; Imamura, Teruhiko; Endo, Miyoko; Kagami, Yukie; Kubo, Hitoshi; Kashiwa, Koichi; Kinugawa, Koichiro; Kyo, Shunei; et al.
Abstract: Background: Two implantable continuous-flow left ventricular assist devices (LVADs), DuraHeart (Terumo Heart, Ann Arbor, MI, USA) and EVAHEART (Sun Medical, Nagano, Japan), were approved in Japan in April 2011. We analyzed the midterm outcome of patients implanted with these implantable LVADs at the University of Tokyo Hospital. Methods and results: A total of 31 patients who underwent implantation of LVADs (10 DuraHeart, 21 EVAHEART) as a bridge to transplantation at our institution between April 2011 and August 2013 were retrospectively reviewed. All patients were followed up through December 2013. Seven patients underwent conversions from NIPRO paracorporeal LVAD (Nipro, Osaka, Japan) to an implantable LVAD. The mean observation period was 483 ± 239 days (41.0 patient years). Eight patients were transplanted and one patient showed functional recovery with subsequent LVAD explantation. Four patients died due to cerebrovascular accident, empyema, or device malfunction due to pump thrombosis after cerebral bleeding. Kaplan–Meier analysis revealed 6-, 12-, and 24-month survival rates of 93%, 86%, and 86%, respectively. The rates of freedom from cerebrovascular accidents and device-related infections at 1 year after LVAD implantation were 65% and 36%, respectively. Twenty-nine patients were discharged home after LVAD implantation. During the period of this study, there were 59 readmissions (53 urgent, 6 elective) among 22 patients (76%). The overall and urgent readmission rates were 1.66 and 1.49 per patient year, respectively. The common reason for readmission was device-related infection (31%), followed by cerebrovascular accidents (17%). The total out-of-hospital time after the primary discharge was 90%. Conclusions: Our midterm survival rate after LVAD implantation is satisfactory. However, patients undergoing LVAD support were often readmitted with adverse events.